THE ROLE OF MOTHER TONGUE IN SUPPORTING EARLY LITERACY DEVELOPMENT: A STRUCTURED NARRATIVE REVIEW AND PEDAGOGICAL SYNTHESIS - Syahrul Riza; Maidar Maidar; Angela Mae Reyes (Sensei International Journal of Education and Linguistic, 2026)
In many places the children speak the local language at home but when they enter the school they must read and write in Indonesian, so it becomes difficult for them. Actually the mother tongue can help them to understand better. This article discusses the role of mother tongue in supporting early literacy development. The method used is literature review from international journals about bilingual education and early reading. The result shows that mother tongue can help the children in oral language, phonological awareness, understanding the meaning, and also make them more confident to speak in the class. But the mother tongue must not be used to replace the school language, it is only a bridge. Therefore the teacher should use the mother tongue to help the children and slowly move to the school language.